PENGARUH BUDAYA ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DI KALANGAN TENAGA CLEANING SERVICE PT ISS INDONESIA - ., DIPRIYANI (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
organizational commitment in the labor Cleaning Cervices PT. ISS Indonesia. The data were collectedby distributing questiounaires to the respondens. the questiounaires distributed to 105 respondents, but only 100 questiounaires that can be analyzed forther. The technique of analysis used was multiple regressions. The result of the research shows that : (1) organizational culture has positive effect on organizational commitment; (2) the job satisfaction also has positive effect on organizational commitment.